2022
DOI: 10.3390/ijerph19116834
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Status of University Students and Working Professionals during the Early Stage of COVID-19 in Bangladesh

Abstract: A novel coronavirus disease known as COVID-19 has spread globally and brought a public health emergency to all nations. To respond to the pandemic, the Bangladesh Government imposed a nationwide lockdown that may have degraded mental health among residents, in particular, university students and working professionals. We examined clinically significant anxiety levels with the Generalized Anxiety Disorder (GAD-7) scale and perceived stress levels with the Perceived Stress Scale (PSS-4) in an online cross-sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 84 publications
1
6
1
Order By: Relevance
“…For example, history of anxiety and/or depressive disorder 41 , governmental measurements aimed at reducing the spread of COVID-19, change in studying format (i.e. forced distant online learning) 42 , worries relating to the health of their family members 43 and worry about social support 44 have been linked to increased levels of anxiety during the COVID-19 pandemic among postsecondary students.…”
Section: Discussionmentioning
confidence: 99%
“…For example, history of anxiety and/or depressive disorder 41 , governmental measurements aimed at reducing the spread of COVID-19, change in studying format (i.e. forced distant online learning) 42 , worries relating to the health of their family members 43 and worry about social support 44 have been linked to increased levels of anxiety during the COVID-19 pandemic among postsecondary students.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have documented the negative impacts of the COVID-19 pandemic on mental health (Banerjee, 2020;Patwary et al, 2022;Rossi et al, 2020;Talevi et al, 2020). Symptoms of depression, anxiety, and psychological disorder became more prevalent due to COVID-19-related structural actions such as lockdowns (Chatterjee et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Since January 2020, there have been over 6,200,000 reported deaths globally [ 2 ]. Although this pandemic has had catastrophic effects on the physical health of millions of individuals, the psychological impact of the virus has also proven detrimental [ 3 , 4 , 5 , 6 ]. The full psychological impact of the COVID-19 pandemic continues to be investigated; however, research has shown that postsecondary students are a population that is highly susceptible to psychological distress [ 3 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although this pandemic has had catastrophic effects on the physical health of millions of individuals, the psychological impact of the virus has also proven detrimental [ 3 , 4 , 5 , 6 ]. The full psychological impact of the COVID-19 pandemic continues to be investigated; however, research has shown that postsecondary students are a population that is highly susceptible to psychological distress [ 3 , 7 , 8 , 9 ]. Young adults between 18 and 24 years of age, the most common age group for postsecondary students, reported the highest levels of pandemic-related psychological distress when compared to other age groups, with a quarter of them reporting suicidal thoughts [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%